The Structure of Protection and Growth in the Late Nineteenth Century - Lehmann, S; O'Rourke, K (MIT Press, 2011)
Many papers have explored the relationship between average tariff rates and economic growth when theory suggests that the structure of protection is what should matter. We therefore explore the relationship between economic growth and agricultural tariffs, industrial tariffs, and revenue tariffs for a sample of relatively well-developed countries between 1875 and 1913. Industrial tariffs were positively correlated with growth, and agricultural tariffs were generally negatively correlated with growth, although the results are not robust. Revenue tariffs were not related to growth at all.